2012
DOI: 10.1021/mp3003607
|View full text |Cite
|
Sign up to set email alerts
|

Solid Nanocrystalline Dispersions of Ziprasidone with Enhanced Bioavailability in the Fasted State

Abstract: Reducing the absorption difference between fed and fasted states is an important goal in the development of pharmaceutical dosage forms. The goal of this work was to develop and characterize a solid nanocrystalline dispersion (SNCD) to improve the oral absorption of ziprasidone in the fasted state, thereby reducing the food effect observed for the commercial formulation. A solution of ziprasidone hydrochloride and the polymer hydroxypropyl methylcellulose acetate succinate (HPMCAS) was spray-dried to form a so… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(6 citation statements)
references
References 27 publications
0
6
0
Order By: Relevance
“…Chemical modification to produce a water-soluble product represents one such approach to solving this problem . One of the physicochemical approaches is to reduce the size of insoluble drug crystals to the nano level in order to increase the available surface area and thus the dissolution rate. Combining porous (and inert) particles as a carrier for hydrophobic drugs also has been reported to improve the bioavailability of a drug. Hydrophobic drug molecules can also be entrapped in O/W emulsion droplets or between lipid bilayers for being administered to the human body in the dissolved state.…”
Section: Introductionmentioning
confidence: 99%
“…Chemical modification to produce a water-soluble product represents one such approach to solving this problem . One of the physicochemical approaches is to reduce the size of insoluble drug crystals to the nano level in order to increase the available surface area and thus the dissolution rate. Combining porous (and inert) particles as a carrier for hydrophobic drugs also has been reported to improve the bioavailability of a drug. Hydrophobic drug molecules can also be entrapped in O/W emulsion droplets or between lipid bilayers for being administered to the human body in the dissolved state.…”
Section: Introductionmentioning
confidence: 99%
“…These studies demonstrated that the probability of achieving the required drug solubilization in the colon with the CCSD concept and thereby the desired once daily pharmacokinetic profile is extremely low. Alternative solubilization technologies for ziprasidone [11,23,56] have subsequently been evaluated. Whilst these could potentially be more promising, these approaches have not been incorporated in a CR dosage form to assess the feasibility of developing a once daily product.…”
Section: Discussionmentioning
confidence: 99%
“…Ziprasidone is poorly water-soluble (free base solubility in pH 6.5 buffered media~0.3 μg/mL), basic (pKa~6), and highly lipophilic (clog P = 3.6) [8][9][10]. These properties combined with a high partition coefficient in bile-salt micelles [11], result in a two-fold increase in absorption of ziprasidone in the fed versus fasted state [12]. However, since no bile-salts are present in the colon to help with absorption of ziprasidone released from a CR dosage form, a solubilized form of ziprasidone is considered necessary for achieving once-daily dosing.…”
Section: Introductionmentioning
confidence: 99%
“…Several other nanocrystalline preparations have also demonstrated enhanced fasted state bioavailability in the fasted state and elimination of food effect in preclinical animal models, including ziprasidone, lurasidone and the novel gamma secretase inhibitor ELND006 . Table contains numerous examples of commercially available nanocrystalline preparations where food effect has been studied.…”
Section: Strategies To Overcome Food Effect Bioavailability In Drug Dmentioning
confidence: 99%